Respons Kubis Bunga (Brassica oleracea var. botritys L) terhadap Jenis Pupuk Organik Cair Pada Berbagai Media Tanam - Eka Rusmiati; Nurleni Kurniawati; Sutomo Sutomo; Rakhmiati Rakhmiati (J-Plantasimbiosa, 2024)
Flowering cabbage is a type of vegetable with high economic value and has a stable selling price, however, production has decreased by up to 10 quintals/ha. One effort to increase the production of cauliflower can be done by providing various liquid organic fertilizers, because they are easily absorbed by plants and contain complete macro and micro nutrients. Land for flowering cabbage cultivation is also limited, so it is necessary to develop cultivation by paying attention to the type of soil and appropriate and supportive planting media. This research aims to determine the effect of POC type and the interaction between POC type and various planting media. This research was carried out at the STIPER Dharma Wacana Experimental Garden, Margorejo Metro Selatan, Metro City at an altitude of 55 meters above sea level, from October to December 2022. This research used an experimental method, with a split plot treatment design consisting of a main plot and subplots. The main plot is a type of liquid organic fertilizer (P) and the sub plots are various planting media (M). Observational data is tested using analysis of variance, similarity of variance can be tested using the Barlett test and non-addictiveness of the data using the Tuckey test, followed by the least significant difference test (LSD) at the 5% level. The results showed that the type of POC did not have a real influence on all the variables observed, while various planting media had a significant influence on the variable number of leaves.